Piggy Pie Po : 3 little stories - Wood, Don, 1945-; Wood, Don (Boston [Mass.] : Harcourt Children's Books, 2010)
Presents the rhyming adventures of Piggie Pie Po.
Accelerated Reader
Keywords: Swine -- Juvenile fiction; Stories in rhyme -- Juvenile literature